Empirical Approaches Upon Pension Systems in Central and Eastern European Countries. Triangle Assessment: Free Movement of People, Labor Market and Population Health Features - Jimon, Ștefania Amalia; Balteș, Nicolae; Dumiter, Florin Cornel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
Nowadays, around the world, it can be noticed an important trend towards the pension system reforms. The creation of the European fiscal space, the effects of globalization and the movement of the labour force are important vectors towards creating a new type of social economy. The labour force is constantly moving around the countries that gathered important amounts of capital, especially in industrialized countries. Moreover, the lower levels of the birth rate combined with the increasing level of death rate unbalance the labour market. The entire European continent undergoes a demographical transition period, highlighted by aging and intensive migration. This phenomenon is registered both outside and inside the European Union, especially upon the highest industrialized Western countries. In this context, the human capital role and quality gain an important topic throughout the social and economic developments. In this article, we tackle some important aspects regarding the correlation between the actual status quo of population structure and some important features of future pension systems.